Inflammatory Myofibroblastic Tumor: A Rarely Seen Submucosal Lesion of the Stomach - Deniz Arslan; Şeyda Gündüz; Deniz Tural; Mükremin Uysal; Ali Murat Tatlı; Cumhur İbrahim Başsorgun; Gülsüm Özlem Elpek; Hasan Şenol Coşkun; Hakan Şat Bozcuk; Burhan Savaş (Case Reports in Oncological Medicine)
Inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal benign tumor which is generally seen in children and in young adults. It is especially located in the lungs. In histopathological examination, neoplastic fusiform cells originating from a subtype of accessory immune system cells which are called fibroblastic reticulum cells are seen (Kouichi and Youichirou, 2008). Although IMT is histopathologically benign, imaging methods show its tendency for local recurrence and invasion. In most of the cases, it may not be possible to make a distinction whether it is malign or benign. Complete surgical resection is the most important treatment method. In this study, we have discussed the findings of our case having a gastric submucosal located IMT in light of the current literatures.